2004
DOI: 10.1177/001698620404800306
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship Between Perfectionism and Achievement Motivation in Gifted College Students

Abstract: This study is a slice of an overarching research investigation of perfectionism in gifted college students. Utilizing a qualitative interview design, this study examined how gifted college students scoring high on 1 of 2 different dimensions of perfectionism (socially prescribed or self-oriented) perceived their achievement motivation. Findings indicated that, for the socially prescribed perfectionists, an underlying motive to avoid failure influenced their achievement goals and behaviors. Based on this motive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 31 publications
4
84
0
7
Order By: Relevance
“…It was therefore of great interest to explore whether the endorsement of different goal orientations could be associated with the endorsement of predominantly positive or negative perfectionism. Consistent with past findings that different forms of perfectionism (self-oriented and socially prescribed) were found to relate differentially to learning, performance-approach, and performance-avoidance goals (Speirs Neumeister, 2004b;Speirs Neumeister & Finch, 2006), the present findings provided further support that positive and negative perfectionism related differentially to different patterns of goal orientations. Specifically, learning and social goals were the significant predictors of positive perfectionism, whereas performance and avoidance goals were the significant predictors of negative perfectionism.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was therefore of great interest to explore whether the endorsement of different goal orientations could be associated with the endorsement of predominantly positive or negative perfectionism. Consistent with past findings that different forms of perfectionism (self-oriented and socially prescribed) were found to relate differentially to learning, performance-approach, and performance-avoidance goals (Speirs Neumeister, 2004b;Speirs Neumeister & Finch, 2006), the present findings provided further support that positive and negative perfectionism related differentially to different patterns of goal orientations. Specifically, learning and social goals were the significant predictors of positive perfectionism, whereas performance and avoidance goals were the significant predictors of negative perfectionism.…”
Section: Discussionsupporting
confidence: 90%
“…They found that most parents reported learning goals, and children of performance-goal parents were significantly more likely to exhibit dysfunctional perfectionism. From a slightly different perspective, Speirs Neumeister (2004aNeumeister ( , 2004b interviewed gifted college students and found that exposure to parental perfectionism and different parenting styles could lead to the development of different types of perfectionists, which in turn could lead to the endorsement of different achievement goals. More recently, Speirs Neumeister and Finch (2006) explored and tested a model connecting parenting styles, attachment, perfectionism, and achievement goals among high-ability students.…”
mentioning
confidence: 99%
“…Berdasarkan kajian literatur, kajian yang melibatkan kumpulan pelajar pintar cerdas adalah terhad dan menghasilkan dapatan yang berkonflik. Neumunster (2004) dalam kajian beliau terhadap orientasi pencapaian dalam kalangan kumpulan pelajar ini. Dapatan ini turut disokong oleh Yoon (2009) yang merumuskan banyak kajian yang meneroka hubungan antara motivasi, aspek kognitif dan pembelajaran kendiri telah mengecualikan kumpulan pelajar pintar ini.…”
Section: Permasalahan Kajianunclassified
“…The other approach is the empirical approach that employs a clustering procedure for classification. This approach has been employed in studies with the HMPS (Speirs Neumeister, 2004;Speirs Neumeister & Finch, 2006) and in studies with the FMPS (Dixon, Lapsley, & Hanchon, 2004;Hawkins, Watt, & Sinclair, 2006;Parker, 1997). For example, Parker (1997) identified in his sample Downloaded by [University of Connecticut] at 13:51 09 October 2014 of academically talented youths three different perfectionist types: nonperfectionists (33%), healthy perfectionists (42%), and dysfunctional perfectionists (25%).…”
mentioning
confidence: 99%